The Role of Christian Music in Preaching the Gospel in Goli Deanery (Colossians 3:16) - Elvis Kutesa (Uganda Christian University, 2024)
This research was carried out in Nebbi District with the aim of examining the role of Christian music in preaching the gospel in Goli Deanery, Nebbi Diocese (ND). It revealed that though modernization has affected the nature and practice of Christian music from preaching the truthful gospel as written in the scriptures to a secular orientation where by some musicians seek to promote their own messages that are not Christ, the good news is that harmonious melodies of Christian music still resonate within Goli Deanery, embracing the divine power of the gospel to reach the hearts of believers and proclaim the eternal message of faith, hope, and love on the ground of Goli Deanery, Nebbi Diocese. The researcher invested the nature and modality of Christian music used in worshipping God in Goli Deanery; the Church practice of using Christian music in preaching the gospel in Goli Deanery; the challenges faced by the Church in using Christian music to preach the gospel in Goli Deanery. Colossians 3:16 emphasizes the necessity of making music to the Lord: "let the message of Christ dwell among you richly as you teach and admonish one another with all wisdom through Psalms, hymns, and songs from the Spirit, singing to God with gratitude in your heart" NIV. The message of Christ. Refers especially to Christ's teaching, which in the time of the Colossians was transmitted orally. But by implication it includes the Old Testament as well as the New Testament. Psalms and Hymns and Spiritual songs. Some of the most important doctrines were expressed in Christian hymns preserved for us now only in Paul's letters. "Psalms" refers to the Old Testament Psalms, some of which may have been set to music by the Church. "Psalms" could also describe a song newly composed for Christian worship, where "hymn" is lit. "Psalm" in the Greek text. A "hymn" was a song of praise, especially used in a celebration, much like the Old Testament Psalms that praised God for all that He is. A "song" recounted the acts of God and praised him for them, much like the Old Testament Psalms that thanked God for all that he had done. See note on Eph 5:19. The investigation was based on this Biblical truth in order to preach the truthful gospel as written in the scriptures. Music brings us into the presence of God, assists us in hearing and responding to the word, helps us experience healing and provides us with the sense of being sent forth. Focusing on God as the source with our gifts of music gives us the ground to declare the truthful message of Jesus in music.
Undergraduate research